Hubungan Lama Rawat Inap dengan Kejadian Depresi pada Anak Usia 10–18 Tahun yang Dirawat di RSUD Dr. Soetomo Surabaya - Rika Hapsari; Mira Irmawati; Ahmad Suryawan; Irwanto (PT Dexa Medica, 2021)
Background: Depression can occur in children with chronic disease who are hospitalized. Prolonged hospitalization correlates with higher prevalence of depression that may affect clinical outcome. The aim of this study is to determine the correlation between length of hospitalization and depression in children with chronic disease. Method: This cross-sectional study was conducted at Dr. Soetomo Hospital Surabaya, from January to March 2019. Children ages 10-18 years with chronic diseases such as oncology hematology, chronic kidney disease, and liver disease hospitalized for ≥7 days were screened for depression. Children with a history of previous depression or other mental illnesses were excluded. Depression was evaluated using the Children’s Depression Ratting Scale-Revised (CDRS-R) questionnaire. Statistical analysis using comparative test and correlation test with p value <0.05. Results: A total of 58 children were treated in the pediatric ward Dr. Soetomo Hospital Surabaya, 50 met the inclusion criteria and 8 were excluded. Subjects consist of 27(54%) boys and 23(46%) girls. The mean age was 11.8±0.39 years. The average duration of treatment was 16±1.6 days. Depression screening found 39(78%) children with varying degrees of depression, 17(34%) moderate depression and 22(44%) severe depression with an average CDRS-R score of 45.2±2.3. The results showed 65.5% of children who were hospitalized for 7-14 days and 95.2% of children who were hospitalized for more than 14 days had depression (OR value=10.52; 95% CI; 1.227-90.311; p = 0.016). Correlation test results between the length of stay and CDRS-R score (r=0.502, p<0.001). Conclusion: Children with chronic disease who are hospitalized more than 7 days have higher risk of depression.